IPTEKS BAGI KTT SAPI POTONG DESA LAU KECAMATAN DAWE KABUPATEN KUDUS YANG MENGHADAPI PERMASALAHAN PENYEDIAAN PAKAN BERKUALITAS - C. I. Sutrisno; B. Sulistiyanto; S. Sumarsih; Cahya Setya Utama (JURNAL LITBANG PROVINSI JAWA TENGAH, 2014)
Targets and outcomes of activities: members of KTT can know and be able to do beef feed management, at least 75% members to provide quality beef cattle feed through the implementation of technology Complete Silage. Evaluation showed that after activity and improved feed management: farmers have standardized requirements for beef cattle feed, farmers were able to formulate quality feed for cattle, ranchers understand feed technology (capable of making complete silage). The impact of these changes are: an increase in body weight gain and finally increased revenue. Conclusion activities can improve the knowledge, insight and skills of farmers in terms of food technology, management and production of beef cattle feed.